A flexibilidade de RH como motivo de adoção de modelos de gestão da saúde pública alternativos ao estatuário: as experiências dos Estados da Bahia, do Paraná e de São Paulo - Fagundes, Maísa Cristina Dante (2018)
The Brazilian Public Administration has been governed by alternating cycles of rigorous and non-rigorous application of legal norms. In the 1990s, with the introduction of reforms in the State apparatus in Brazil to reflect the worldwide movement, the State profile was changed to suit contemporary reality, and relaxation of legal norms that undermined the decision-making power of the public manager was sought. Legal norms had become more rigid with the adoption of the Federal Constitution of 1988. The masterplan for reforming the State apparatus (PDRAE) established flexibility mechanisms, including transfer of responsibility of non-exclusive state activity to non-state public or private entities. Subsequent years witnessed the creation of public entities and establishment of partnerships and contracts involving both non-state public entities (philanthropic) and private organizations (corporations). Next, social organizations, the new strand of autonomous social services, public-private partnerships, and several state foundations emerged. However, there was great opposition to these new management models. Representative bodies of workers claimed that “privatization” of public services only contributed to job insecurities. The controlling agencies, in turn, hardened their stance and reduced the reach of the few flexibilities provided. However, governments continued to use these models, especially in public health, the area chosen for analysis in the present study. Thus, is it possible to conclude that the quest for flexibility is the main reason for adopting new management models? If so, which flexibility? As human resources is a sensitive aspect in the health field encompassing the provision of services in a field where presence of people is fundamental, we decided to analyze the adoption of these models based on the flexibility of human resources (HR). To this end, we analyzed three emblematic cases of Brazilian states using a qualitative approach: the first national public-private partnership in the health field in Bahia; the successful state-owned foundation of Paraná; and social organizations in São Paulo. Semi-structured interviews were conducted and documents were analyzed to assess whether contractual flexibility is the decisive factor in the adoption of these labor management models in public health, as an alternative to the statutory model. The selected samples were analyzed according to the human resources flexibility framework developed by Francisco Longo (2007). It was possible to conclude that even though flexibility is seen in the models analyzed, the model was adopted only for its broader aspect of flexibility, limited to the easing of regulatory rigidity.